(untitled) (Research, Society and Development, 2023)
This article describes the impact of the COVID-19 pandemic on notifications of acute febrile diseases (AFD) Dengue, Yellow Fever, Human Visceral Leishmaniasis (LVH), Leptospirosis and Malaria in a Reference Hospital in Infectious Diseases in Goiás. This is a cross-sectional study carried out from secondary data obtained at the Hospital Center for Epidemiological Surveillance and patients records admitted to the institution covering the period 2019 to 2020. In the period evaluated, 144 patients were hospitalized for COVID-19, 600 for Dengue, 34 for LVH, 17 for Leptospirosis and 36 for Malaria. The diseases were prevalent in male, in black race, and in urban area residents. Deaths were observed in pacients affected by COVID-19 (46) and Dengue (8). Reduction in AFD notifications was also observed during the first year of pandemic (2020). Actions aimed at controlling the COVID-19 pandemic may have contributed to the reduction of AFD notifications in 2020.